(untitled) (Journal of Economic Research & Business Administration, 2015)
The modern system of management of marketing in addition to the priority of the market orientation of the production of goods and services involves the formation of positive public opinion, enhancing innovation, high standards of service, availability of safety standards and reputation of top management as an invaluable capital. The article deals with the quality of marketing companies. Quality Marketing is multifactorial characteristic results of all the participants of the market turnover. Marketing is a mirror image of the results of all parts of the scope of companies. That stage of consumption shows the quality of life of the community, the level of safety and service of the national economy. In modern conditions for gaining a strong market position is crucial quality parameters such as marketing provider, consumer marketing, service, customer service efficiency, quality of communication, socio-economic activity and image.